PERSPECTIVES ON USE OF BEVACIZUMAB IN PATIENTS WITH NEUROENDOCRINE TUMORS. CASE REPORT - G. S. Emelianova; N. F. Orel; V. A. Gorbunova; A. A. Kolomeytseva; A. A. Kuznetsova; A. E. Kuzminov; A. A. Fedenko (Сибирский онкологический журнал)
Advanced well differentiated neuroendocrine tumors (NET) have poor sensitivity to chemotherapy. Biotherapy and targeted therapy are the main treatment options for these patients. Approaches to the 2nd and subsequent lines of treatment have not been developed to date. VEGFR blocker bevacizumab is actively studied in well differentiated NET. For well differentiated NET, it has been shown that an increase in VEGF expression is associated with metastasis and decrease in progression-free survival.